Forest birds maintain body condition in Alder-leaf Birch (Betula alnoides) plantations in subtropical Asia - Wenyi Zhou; Alexandra A. Grossi; Daniel R. Gustafsson; Zhengzhen Wang; Zhuyang Zhang; Yuqing Han; Xinyi Wang; Anru Zuo; Miguel A. Acevedo; Yang Liu; Scott K. Robinson (Basic and Applied Ecology)
Plantation forestry alters avian community assembly by creating homogeneous habitats with simplified vegetation structure. However, its effects on avian body condition remain poorly understood, despite the influence body condition has on survival and reproduction. We studied how plantation forestry of Alder-leaf Birch (Betula alnoides, “birch”) affects the body condition of nine forest bird species in the Indo-Burma biodiversity hotspot in southwestern China. Through mist-net sampling, we collected data on avian body condition in birch plantations and natural forests of two age classes (young and mature). We also examined other factors that might affect body condition including demographic information (age and sex), previous-day weather (rainfall and temperature), and reproductive status. Body condition scores measured using the scaled mass index (SMI) were similar between birch plantations and natural forests, indicating that birch plantations support avian body condition at levels comparable to natural forests. Age and rainfall affected the body condition of Yunnan Fulvettas (Alcippe fratercula), with adults and individuals captured after rainfall having lower SMIs. Additionally, the body condition of Rusty-capped Fulvettas (Schoeniparus dubius) and Silver-eared Mesias (Leiothrix argentauris) was positively associated with their reproductive status, though the higher SMI values may partly result from gonadal and egg development. Our study reveals not only the conservation value of birch plantations but also the effects of demographic, environmental, and reproductive factors on avian body condition. We recommend considering birch as a candidate timber species for promoting conservation in plantation forestry.